Cerium oxide nanoparticles attenuates fibrosis and inflammation in thyroid-associated ophthalmopathy via JNK pathway - Wang, Bo-Wen; Zhu, Ru; Jin, Ying; Ouyang, Xuan; Jiang, Fa-Gang; Wang, Xing-Hua (Frontiers in Molecular Biosciences, 2025)
ObjectiveThyroid-associated ophthalmopathy (TAO) is an autoimmune orbital disorder characterized by pathological alterations including extraocular muscle fibrosis and orbital inflammation. Cerium oxide nanoparticles (CeO2-NPs, CNPs) are gaining popularity in ophthalmology due to their potential antifibrotic and anti-inflammatory properties. This study aims to investigate the inhibitory effects of CNPs on fibrosis and inflammation in TAO orbital fibroblasts (OFs) derived from TAO patients.MethodsOFs obtained by primary culture of orbital adipose tissue from 8 TAO patients. Probing the safe action concentration of CNPs and Anisomycin using CCK8 and detecting intracellular reactive oxygen species (ROS) generation using ROS Assay kit. Wound-Healing Assay was used to examine the degree of fibrosis of OFs. The expression of Fibronectin, COL1A1, α-Smooth muscle action, Hyaluronan Synthase 2, c-Jun N-terminal Kinase (JNK) and pJNK were detected by the RT-PCR and WB, and Hyaluronic Acid secretion was detected by ELISA. Inflammatory factors Interleukin-6 (IL-6) and Tumor Necrosis Factor-α (TNFα) expression were detected by RT-PCR and ELISA.ResultsCNPs below 100 μg/mL and Anisomycin below 5 μM did not affect OFs proliferation. CNPs inhibit intracellular ROS generation. CNPs inhibit OFs fibrosis and suppress the expression of fibrosis indicators. These antifibrotic effects were mediated by inhibition of JNK phosphorylation, and were reversible by a JNK agonist. Furthermore, CNPs reduce both mRNA levels and secretion of inflammatory factors, IL-6 and TNF-α.ConclusionCNPs demonstrated the ability to inhibit fibrosis in TAO OFs by reducing JNK phosphorylation, as well as dose-dependently suppressed ROS generation and inflammatory response in TAO OFs.